Faktor-Faktor Psikologis yang Mempengaruhi Kebahagiaan pada Lanjut Usia Suku Jawa di Klaten - Ahmad Muhammad Diponegoro; Mulyono Mulyono (Universitas Ahmad Dahlan, 2015)
This study aims to determine the psychological factors that affect happiness elderly Javanese in Klaten. The approach used qualitative phenomenological study types. Data collection techniques by observation and interviews of the three objects. The object of research is intended that three grandparents (elderly) aged 85 years. Two elderly widowers and the elderly are still married which seemed to live in harmony (harmony). The whole object of research is Muslim, diligent prayer, living in the village, and all living in a home with children, grandchildren, and law. The results of this study indicate that there are 14 factors that affect happiness elderly (earnings; age; religion; culture; thanks to the Lord; physical activity; social relationships; forgiveness; quality of life; Hospitality; healthy; married; relate well to children, grandchildren, and daughter, as well as a good relationship with the brothers) and there are 13 of affects that affects happiness elderly (feel happy, patient, calm atmosphere, optimistic, calm serene, feel compassionate, considerate, passionate, not revenge, relaxed, polite, happy to help / give, and not afraid of death / resignation to fate of old age). Based on the research results it can be concluded that there are 14 and 13 affective factors that affect happiness elderly and considers that it is important for them. The results of this study for the families of the elderly and the community to take a stand in the face and continually meet the needs of the elderly. Furthermore, the results also useful for counselor as a material consideration in implementing gerontology counseling (counseling elderly) in order to achieve elderly to get happiness.